Growth performance of local and genetically improved chicken of Bangladesh: Growth and Carcass characteristics of Bangladeshi chicken - Akhter, A; Das, SC; Hasan, MS; Akter, T; Sultana, M; Faruque, S; Rashid, MA; Dey, B; Hossain, MA; Akter, S; Retee, NN (Bangladesh Journal of Animal Science, 2018)
The experiment was conducted to compare the growth performance among four genotypes of indigenous chicken namely Non-descriptive Native (ND), genetically Improved Native (IN), Hilly (HC) and Naked Neck (NN) of Bangladesh under free-range rearing system. A total of 288 day old chicks (DOC) from four genotypes were divided into four treatments having eight replications of each for a period of 12 weeks under free-range system with supplementation of commercial broiler diet. During first 4 weeks, all chicks were kept together, whereas chicks of ND was brooded in the same room but separated by a partition. At 5 weeks of age chicks were randomly distributed to the selected farmers. Growth parameters were recorded to determine the comparative growth performance among four genotypes of chicken. The highest body weight (1110.76 g/bird) was achieved by HC, followed by IN (900.63 g/bird) and NN (831.13 g/bird) at 12 weeks of age. The lowest body weight (734.13 g/bird) however was found in ND chicken. During the growing period under free range rearing (5-12 weeks), HC group consumed the highest amount of feed (2697.02 g/bird) with an average FCR of 3.06 while the lowest feed consumption (2666.13 g/bird) with the highest FCR of 4.90 was observed in ND. IN consumed (2674.63 g/bird) feed with an average FCR of 3.92 and BLRI improved NN consumed (2668.13 g/bird) feed with an average FCR of 4.19. Live weight gains in all the four genotypes of indigenous chicken were changed almost in a similar pattern. Significant differences were observed in live weight, dressing percentage, breast meat, drumstick, thigh meat among the four genotypes of chicken. The HC was superior to other genotypes of indigenous chicken including ND in terms of growth performance, meat yield characteristics and net returns. Bang. J. Anim. Sci. 2018. 47 (2):76-84